GROWTH OF CARBON NANOTUBE BYAPPLYING ION IMPLANTATION TECHNIQUE - Salim Mustofa; Yunasfi Yunasfi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
GROWTH OF CARBON NANOTUBE BYAPPLYING ION IMPLANTATION TECHNIQUE. The use of ion implantation technique for growing carbon nanotubes (CNT) has been studied. Implantation technique with its high and focused energy is used for implanting Ni+ ion, which can act as catalyst for CNT growth. CNT was grown by implantation of Ar+ and Ni+ ion to the nanostructured carbon thin film that were deposited on Si(100) substrate. The dose of ion implantation parameter was varied between 5 x 1015 to 1 x 1017 ion/cm2. After implantation, the phase identification by X-Ray diffraction (XRD) and observations of surface and cross section morphology of samples by Scanning Electron Microscopy (SEM) in order to investigate the growth of CNT were carried out. The XRD analysis shows the peak of C(002), Ni(010) and Si(100) on the C/Si thin film samples after ion implantation, which indicate the carbon film still in a crystalline structure. The peak of Ni(010) is slightly decreased with the increasing of ion dose. The observation by SEM shows that the greater the dose of implants, the more unflat surface found on a thin film. While from the observation of cross section, it was indicated that the higher dose implants, more clearly the growth of CNTs on the surface of C/Si thin film. CNT is predicted to grow as a result of interaction between ion radiations with carbon, leading to the formation of CNTs.